Pengembangan Media Pembelajaran Interaktif “Biolens Fungi” Berbantuan Website pada Mata Pelajaran Biologi Kelas X SMA - Fajar, Muhammad Ardi; Rayendra; Zen, Zelhendri; Darmansyah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The low scientific literacy and students' difficulties in visualizing the microscopic and abstract structure of fungi indicate the need for interactive digital learning media that supports visual understanding. This study aims to develop a website-based interactive media